ANALISIS PERNIKAHAN USIA DINI REMAJA PEREMPUAN DI DESA JAWAI LAUT KECAMATAN JAWAI SELATAN KABUPATEN SAMBAS - Novitasari, Delfia; Bahari, Yohanes; Asriati, Nuraini (Jurnal Pendidikan Sosiologi dan Humaniora, 2021)
This research is entitled Analysis of Early Childhood Marriage for Girls in Jawai Laut Village, South Jawai District, Sambas Regency. The purpose of this study was to determine the causes and effects of early marriage and the impact of early marriage by adolescent girls in Jawai Laut Village, South Jawai District, Sambas Regency. Sources of data in this study were teenage girls who married at an early age. The results of this study indicate that the factors that cause early marriage in Jawai Laut Village, South Jawai District, Sambas Regency are the low level of economy and education level. Factors that also encourage early marriage in the village of Jawai Laut, South Jawai District, Sambas Regency, are due to the accident factor (married by accident) before they got married. Early marriage has an impact on adolescent girls who marry at school age because they are pregnant before marriage, then the impact of losing the opportunity to complete a better education.